2008
DOI: 10.1002/eji.200838331
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 10 suppresses Th17 cytokines secreted by macrophages and T cells

Abstract: IL‐17 and IL‐22 are typical cytokines produced by the Th17 T cell subset, but it is unclear if Th17 cytokines can be produced by other cell types. We demonstrate that IL‐10‐deficient and IL‐10R‐deficient macrophages stimulated with lipopolysaccharide produce high levels of IL‐17 and IL‐22. Addition of exogenous IL‐10 to IL‐10‐deficient macrophages abolished IL‐17 production. When IL‐10‐deficient and IL‐10R‐deficient splenocytes were cultured under Th17 polarizing conditions, the population of IL‐17‐producing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
171
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(189 citation statements)
references
References 18 publications
(20 reference statements)
15
171
2
Order By: Relevance
“…IL-2 or IL-10 signaling has been shown to modulate Th17 cell generation (19,20); however, in the present study, impaired IL-17 production in Myd88 −/− CD4 + T cells was not related to increased IL-2 or IL-10 production (Fig. S2).…”
Section: Resultscontrasting
confidence: 69%
“…IL-2 or IL-10 signaling has been shown to modulate Th17 cell generation (19,20); however, in the present study, impaired IL-17 production in Myd88 −/− CD4 + T cells was not related to increased IL-2 or IL-10 production (Fig. S2).…”
Section: Resultscontrasting
confidence: 69%
“…However, new cellular sources have been proposed, such as macrophages, neutrophils, and CD8, NK, ab, and gd T cells (13)(14)(15). In this study, we demonstrated that among the IL-17A-producing cells recruited upon silica treatment in the lung, only gd + and CD4 + T cells significantly expressed IL-17A.…”
Section: Discussionmentioning
confidence: 56%
“…CD4 + T cells are not the only source of IL-17 and -22; gd T lymphocytes also produce considerable quantities of these cytokines in different neutrophilic reactions. NK T cells and CD8 T cells were also identified as IL-17-producing cells that contribute to neutrophil recruitment through IL-17 secretion (13)(14)(15).…”
mentioning
confidence: 99%
“…Furthermore, exposure of human macrophages to IL-10 induces IL-10R mRNA transcription [22]. Most recently, the production of Th17 cytokines by macrophages and its suppression by IL-10 was shown in vitro using IL-10R2 deficient macrophages [23]. By using IL-10R1 knock-out mice, we could confirm that the suppression of IL-17 production is IL-10 specific and that monocytes/macrophages are the main targets of IL-10 in the regulation of the Th17 cytokine production.…”
Section: Conditional Inactivation Of the Il-10r1 Genementioning
confidence: 99%